Business Consulting para la empresa sociedad minera Cerro Verde S.A.A. - Perez Cortez, Pedro Estuardo (2024)
This report presents the analyzes carried out by the Business Consulting team on the situation of the Cerro Verde Mining Company, located in Arequipa, Peru. The company, part of the Freeport-McMoRan Copper and Gold group, stands out for its commitment to sustainable and responsible mining practices, as well as its contribution to local economic and social development. However, challenges related to overstock management were identified, including environmental contamination, storage costs and negatively impacted cash flow. The proposed solution involves the implementation of a web platform to showcase and market available excess stocks to other companies. This initiative not only addresses the identified problems, but is also economically viable, with positive financial impacts on the company. The implementation of this web portal provides a centralized channel for the sale of spare parts and unused mining equipment, improving the visibility, accessibility, and process efficiency. Additionally, it promotes sustainability by encouraging the reuse of equipment rather than disposal. In summary, the implementation of this platform not only optimizes the management of overstocks, but also contributes to a more sustainable and efficient approach to management of spare parts and unused mining equipment at Minera Cerro Verde.